2019
DOI: 10.1002/hed.25623
|View full text |Cite
|
Sign up to set email alerts
|

The combined use of EFS, GPX2, and SPRR1A expression could distinguish favorable from poor clinical outcome among epithelial‐like head and neck carcinoma subtypes

Abstract: Background We aimed at identifying molecular markers predictive of clinical outcome in patients with head and neck cancer based on the expression profile of cells showing epithelial‐like (EL) or mesenchymal‐like (ML) phenotypes. Materials and methods We analyzed the association between EL and ML cells and migration, drug resistance, or tumor growth. The differential gene expression profile between cell types was used to build a model to stratify patients according to survival. Results EL cells were sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
(169 reference statements)
2
6
0
Order By: Relevance
“…After adjusting for confounding factors, it was demonstrated that the expression of SPRR1A was an independent predictor for OS. In accordance with previous findings (10,11), these results revealed the prognostic implication of SPRR1A in colon cancer. A tendency was indicated between high SPRR1A expression and the incidence of distant metastasis (high expression vs. low expression, 15.9% vs. 3%); however, no significant differences were indicated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…After adjusting for confounding factors, it was demonstrated that the expression of SPRR1A was an independent predictor for OS. In accordance with previous findings (10,11), these results revealed the prognostic implication of SPRR1A in colon cancer. A tendency was indicated between high SPRR1A expression and the incidence of distant metastasis (high expression vs. low expression, 15.9% vs. 3%); however, no significant differences were indicated.…”
Section: Discussionsupporting
confidence: 93%
“…Relapse-free and disease-free survival indicated no tumor recurrence in patients. such as diffuse large B-cell lymphomas (9), head and neck squamous cell carcinoma (10) and breast (12) cancer. Leclerc et al (12) reported high expression of SPRR1A in a murine preneoplastic intestine and in the normal intestinal mucosa of patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPRR genes encode a class of polypeptides (small proline rich proteins) that are involved in differentiation of keratinocytes, the primary cell type of the epidermis. SPRR1A is known to play a role in various types of cancer, such as diffuse large B-cell lymphomas [ 39 ], head and neck squamous cell carcinoma [ 40 ], and breast cancer [ 41 ]. The overexpression of SPRR1B has been shown to enhance the entry of cells in the G0 phase of the cell cycle [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…(C and D) Tumor volumes were measured every five days and calculated as described in the Method section, which revealed that SPRR2B-shRNA significantly attenuated tumor growth while overexpressing SPRR2B exerted opposite effects. malignancy progression, such as SPRR1A, [25][26][27][28] SPRR1B, [29][30][31] SPRR2A, [32][33][34][35] and SPRR3. [36][37][38][39] However, SPRRs can serve as either tumor suppressors 39 or oncoproteins 38 in different malignancies.…”
Section: Discussionmentioning
confidence: 99%